Financial and analytical activities as the foundation for managing financial and material resources of enterprises - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2024)
The article focuses on developing new scientific solutions to examine the impact of financial and analytical activities on managing financial and material resources at Ukrainian enterprises. The necessity of enhancing the efficiency of financial and analytical activities in the management of financial and material resources at Ukrainian enterprises has been highlighted. The aim of the article is to reveal the depth and directions of the practical impact of financial and analytical activities on the management of financial and material resources at Ukrainian enterprises in the context of the country’s economic transition to a post-industrial development model and the fight against Russian military aggression. Methodology: a combination of general and specialized methods at both the empirical and theoretical levels was used. These included literary analysis to define the essence of key terms such as "activity," "financial activity," "analytical activity," "management," "financial resources," "material resources," "financial resources management," "material resources management," and "financial and analytical activity at the enterprise"; abstraction to identify the relationship between financial and analytical activity and the management of financial and material resources within an enterprise; induction and deduction to determine the directions in which financial and analytical activity influences the management of financial and material resources at the enterprise; analysis and synthesis to develop ways to enhance the efficiency of financial and analytical activities and their impact on managing financial and material resources at the enterprise; the methods of systematization, grouping, and logical generalization to organize information, draw conclusions, and develop scientific proposals presented in the article. Results: the depth and directions of the effective influence of financial and analytical activities on the management of financial and material resources at Ukrainian enterprises in the context of the country’s economic transition to a post-industrial development model and the fight against Russian military aggression have been revealed. JEL Classification: D21, D 80, D 83